TRANSFORMING CHARACTER EDUCATION THROUGH THE MADRASAH LITERACY MOVEMENT: ENCOURAGING READING INTEREST AND HABITS - Maryanto, Maryanto; Qodriyah, Khodijatul; Thelma, Chanda Chansa (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to find out the implementation of the School Literacy Movement at MI Syu'batulkholafiyah, Jatiurip Village, Krejengan District, Probolinggo, and 2) identify supporting and inhibiting factors in the implementation of school literacy activities at the school. This study used a qualitative descriptive approach involving direct observation, interviews, and documentation as data collection methods. The results of the study indicate that the implementation of literacy at MI. Syu'batulkholafiyah, Jatiurip Village, Krejengan District, Probolinggo has generally undergone the three stages. The habituation stage can be seen in the morning reading routine, the development stage is reflected in using various books in the classroom, and the learning stage is implemented through literacy activities integrated into subjects. The main supporting factors in implementing GLS are teacher commitment and active student participation while inhibiting factors include limited facilities and lack of parental support in supporting literacy activities at home. Overall, this school's literacy movement contributes significantly to forming a character of reading in students. However, challenges still need to be overcome to increase its effectiveness..